2021
DOI: 10.1007/978-3-030-71151-1_50
|View full text |Cite
|
Sign up to set email alerts
|

Using Nonlinear Normal Modes for Execution of Efficient Cyclic Motions in Articulated Soft Robots

Abstract: Thanks to their body elasticity, articulated soft robots promise to produce effective and robust oscillations with low energy consumption. This in turn is an important feature which can be exploited in the execution of many tasks, as for example locomotion. Yet, an established theory and general techniques allowing to excite and sustain these nonlinear oscillations are still lacking. A possible solution to this problem comes from nonlinear modal theory, which defines curved extensions of linear Eigenspaces cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The results are stable hyper-efficient natural oscillations. However, these techniques have had a primarily theoretical development and were validated on simple systems and exclusively in simulation -except for the preliminary work [26].…”
Section: Introductionmentioning
confidence: 99%
“…The results are stable hyper-efficient natural oscillations. However, these techniques have had a primarily theoretical development and were validated on simple systems and exclusively in simulation -except for the preliminary work [26].…”
Section: Introductionmentioning
confidence: 99%
“…Within first principles-based models, two subcategories emerge. Della Santina et al (2018a) and others (Bruder et al, 2017(Bruder et al, , 2018bDella Santina et al, 2018b;Satheeshbabu and Krishnan, 2017;Tondu and Lopez, 2000) show that lumped-parameter models can be used in design and control tasks. Continuum mechanical formulations have recently been demonstrated to be useful in soft system design and control (Coevoet et al, 2017;Connolly et al, 2017;Deimel and Brock, 2016;Goury and Duriez, 2018;Moseley et al, 2016;Polygerinos et al, 2015b;Uppalapati et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, a similar experiment as presented here had suggested that a bang-bang control law could represent the human behavior [25], which showed to work robustly and optimally efficient in robotic systems [23, 24, 26]. Thus, this control strategy is likewise considered as a possible excitation approach of the human and applied in simulation to obtain a third baseline for comparison.…”
Section: Resultsmentioning
confidence: 75%